Porous polytrimethylenecarbonate scaffolds: Design considerations and porosity modulation techniques - Klaudia Małgorzata Jurczak; Ruichen Zhang; Wouter L.J. Hinrichs; Dirk W. Grijpma; Richte C.L. Schuurmann; Jean-Paul P.M. de Vries; Patrick van Rijn (Materials & Design)
Porous materials are vital for tissue engineering scaffolds as scaffolds with interconnected pores support functions like nutrient exchange and cell–cell communication. The degree of porosity and pore size distribution directly influences mechanical properties, affecting cell proliferation, migration, and tissue vascularization. Obtaining a balance between mechanical robustness and mass transport capabilities is crucial for any scaffold systems used in tissue engineering. Still, the optimal inclusion of porosity depends on many factors and can be complex and vary greatly between systems. Here we focus on the design principles of porosity in the biodegradable polymer poly(trimethylene carbonate) (PTMC) by comparing three fabrication methods: salt leaching, freeze drying, and freeze extraction. Various parameters, such as solvent type, salt type, polymer-salt ratio, polymer concentration, freezing temperature, and water content, were investigated during PTMC film preparation. Scanning electron microscopy (SEM) and JMicroVision software were employed to analyze film morphology and porosity. The study revealed that the porosity modulation technique significantly impacted the final porosity of PTMC, with variations observed between the top and bottom sides of the film. The project successfully identified an optimal method for inducing porosity in PTMC films, offering potential applications in tissue engineering for regenerative purposes.